Predictors of Recovery from Depression and Anxiety in Women: A Longitudinal Study from Childbirth to 6 Years. (May 2017) - Shankar, Radhika; Badker, Rinette; Brain, Ursula; Oberlander, Tim F.; Misri, Shaila
Objective: This study prospectively examined maternal biopsychosocial predictors of recovery from comorbid depression and anxiety from 25 weeks' gestation to 6 years postbirth. Specifically, the study investigated the influence of 1) maternal factors and 2) the child's behaviours and physical health on the course of the mother's depressed mood and anxiety. Methods: Eighty-six women diagnosed with antenatal depression/anxiety were recruited through the Reproductive Mental Health Program and family practices in Vancouver. Based on the trajectory and status of their symptom remission, participants were categorised into 3 groups: full recovery, partial recovery, and no recovery. The following measures were completed over 6 years: Hamilton Anxiety Rating Scale (HAM-A) and Hamilton Depression Rating Scale (HAM-D) at baseline; Parental Stress Index (PSI) added at 6 months postpartum; Beck Anxiety Inventory (BAI), Beck Depression Inventory II (BDI-II), and Child Behavior Checklist (CBCL) at 3 years postbirth; and HAM-A, HAM-D, MacArthur Health and Behavior Questionnaire (HBQ-P), and PSI at 6 years postbirth. Results: Factors that predicted full recovery from depression included the absence of maternal health concerns, low total parental stress, and few child behavioural issues, whereas low levels of spousal stress were a significant factor in achieving full recovery from anxiety. Conclusion: A variety of maternal and child-related factors govern full recovery or sustained remission of depression/anxiety in the postpartum up to 6 years postbirth. Early awareness of these predictors could lead to timely interventions, ensuring long-term maternal-child well-being.